(untitled) (Bangladesh Journal of Urology, 2022)
Objective: To compare the efficacy of Holmium laser and pneumatic lithotripsy for the treatment of lower ureteric calculi. Methods: The study included total of 218 patients divided into two groups of laser lithotripsy (LL) and pneumatic lithotripsy (PL). Study was conducted between October 2014 and September 2018. Inclusion criteria were patients with a lower ureteric single stone of size 0.8 to 1 cm and negative urine culture. An x-ray KUB and USG of KUB was mandatory. IVU also done when required. Procedures were done under spinal anesthesia. A 9.5 Fr. semi rigid ureteroscope was used for ureteroscopy in all cases. Holmium laser with 550 ìm fiber was employed in laser group and frequency was set between 20-30 Hz at energy of 0.5 to 1 Joule. Storz lithotripter was used in PL group. Postoperatively patients underwent radiography at 4th week of follow up to assess stone clearance. Results: The mean patient age in LL and PL group was 38.8±9.1(15-58) and 41.2±10.3(16-62) years, male to female ratio 1.75:1and 1.57:1 and stone size 8.94±0.98 and 8.94±0.91 mm respectively. Stone free rate at 4 weeks was 96.36 % in LL group as compared to 88.83 % in PL group(p=0.033). Stone migration up in pelvicalyceal system occurred in one (0.90%) patients of LL group while in five (4.63%) patients of PL group (p= 0.0929). DJ Stent was placed in 43(39.09%) patients in LL group whereas 64(59.25%) patients required it in PL group (p=0.0030). Complication rate was 18.18% (20) in LL group whereas it was 38.88% (42) in PL group (p=0.0038) Conclusion: Holmium laser lithotripsy is a superior technology compared to pneumatic lithotripsy in terms of rate of stone clearance and complications for lower ureteric stones. Bangladesh J. Urol. 2021; 24(1): 14-19